Poly-γ-glutamic acid enhances the wheat yield, water use efficiency and soil physicochemical properties of the arid area in the Northwest China. Issue 13 (10th November 2023) - Shi, Wenjuan; Yue, Xiulu; Liang, Jiaping; Wen, Lijun; Li, Jiake; Li, Na; Lu, Yanwei
ABSTRACT: Poly-γ-glutamic acid (γ-PGA) is an environment-friendly super absorbent polymer that can be used as a soil conditioner, which is promising to improve crop productivity and cope with soil degradation. The objectives of this study are to study the effects of γ-PGA on soil physicochemical properties and winter wheat ( Triticum aestivum L. cv. Xinong 975) production in arid region of Northwest China. According to the mass ratio of γ-PGA and soil, experiment treatments consisted of four different γ-PGA application rates, which were designated as 0 (CK), 0.05% (P0.05), 0.1% (P0.1), and 0.15% (P0.15), respectively. The mixed soil samples were uniformly filled into identical plastic pots. Each treatment had three replicates randomly distributed within 12 pots. The results indicated that γ-PGA significantly increased saturated water content by 6.3-11.5%, field capacity by 8.4-15.3%, and plant available water by 5.1-12.5% compared with the CK. γ-PGA increased soil NO3 − -N content and residue, and enhanced the proportions of soil macro-aggregates compared with the CK. γ-PGA increased winter wheat yield by 29.3-34.7%, and WUE by 21.2-33.3% compared with the CK. The main conclusion γ-PGA application amount of 0.05-0.1% can be used to improve soil physicochemical properties and winter wheat production in degraded soil.